On the convergence of fixed-step power control algorithms with binary feedback for mobile communication systems. - Dongwoo Kim (IEEE Transactions on communications)
The mobile transmitter power control algorithms that need to exchange the tract information on link gains, interference levels, or signal-to-interference ratio (SIR) between transmitters and receivers have been proved to converge to a unique fixed power allocation. However, such exact exchange requires an excessive bandwidth for signalling traffic. In practical systems, only 1 bit is sent back to each transmitter. The 0-1 binary feedback is used by the transmitter either to increase or to decrease the power level by a predetermined amount. In this study, we prove a convergence property of the binary feedback power control algorithm. Since the power level of each transmitter is changed by a fixed amount at every iteration, we cannot claim that the power converges to a fixed point. Instead, we show that the received SIR of each user falls within a certain specific range that is determined by an SIR target and a power control step-size